Hepatic Subcapsular Hematoma In Hellp Syndrome Managed By The Maternal Perinatal National Institute, Between 2004-2014 - Gonzales-Carrillo, Oswaldo (2016)
Objective. To determine the clinical and management features of hepatic sub capsular hematoma (HSH) as a result of severe preeclampsia and HELLP syndrome in the period between 2004 and 2014. Materials and methods. We reviewed the cases with HSH in our institution retrospectively. Clinical features, diagnosis, medical and surgical management were defined. Search also included PubMed. The results of our study were compared with those already published.